Process Simulation and Techno-Economic Assessment of Vinasse-To-Biogas in Cuba: Deterministic and Uncertainty Analysis - Pages-Diaz, J (Institution of Chemical Engineers, 2021)
This paper presents a process simulation model in Aspen Plus® and a techno-economic assessment for the anaerobic digestion of Cuban sugarcane vinasses considering three scenarios for biogas application: electricity production (S_1), biomethane as vehicle fuel (S_2), and biomethane for gas grid injection (S_3). From the simulation model, non-significant differences (p_value ≥ 0.1779) between experimental and simulation results were found. S_1 showed the best economic performance among the assessed biogas applications. From the sensitivity analysis, the mean electricity price leading to a net present value of zero for S_1 was 90 USD/MWh, while for S_2 and S_3 the mean incentive required was 0.33 USD/m3biomethane and 0.67 USD/m3biomethane, respectively. The uncertainty analysis showed a chance for investment failure in S_1 less than 10%, whereas for S_2 and S_3 it ranged between 31–37%. The minimum scale required (milling and distillery capacities, ethanol yield) for getting profits from biomethane projects was targeted at 10,800 tcane/day, 108 m3ethanol/d at 10 Lethanol/tcane, respectively. To this end, Cuban plants should significantly increase their average capacities; otherwise, a centralized biomethane production by limiting the number of biomethane plants to one or two per province could be implemented. © 2021 Institution of Chemical Engineers